ANALISIS PENGENDALIAN PERSEDIAAN MENGGUNAKAN METODE FORECASTING DAN EOQ: Studi Kasus: UMKM Keripik Silada Gurih di Cikalongwetan - Meilany Sekarwangi; Rediawan Miharja (LPPM Universitas Sains dan Teknologi Komputer, 2024)
This research aims to analyze inventory control at UMKM Keripik Silada Gurih using forecasting and Economic Order Quantity (EOQ) methods. The research method employed is a quantitative method with a descriptive approach, using numerial data to analyze to the total minimum inventory costs. The result indicate that the 3-month Moving Average forcasting accuracy and reducing total inventory costs. The EOQ method also shows potential for optimizing order quantity and frequency, with the calculation results showing an optimal order quantity of 294 kg and an ordering frequency of 73 times per year. The combination of these two methods significantly enhances inventory control efficiency compared to the conventional methods previously used.